Monitoring treatment response in sputum smear positive pulmonary tuberculosis patients: Comparison of weight gain, sputum conversion and chest radiograph - How, Soon Hin; Kuan, Yeh Chunn; Ng, Teckhan; Razali, M. R A (Malaysian Society of Pathologists, 2014)
Background: Monitoring treatment response to anti-tuberculous therapy remains unsatisfactory in resource-limited countries where sophisticated and expensive tests are not readily available. Sputum culture for mycobacterium is desirable, but not obtainable in many developing countries. Sputum acid-fast bacilli (AFB) smear alone can be misinterpreted in the presence of unviable bacilli or non-tuberculous mycobacteria. Hence the search for a cheaper but reliable monitoring tool, or a combination of several tools, continues. Interesting reports from studies in third world nations have considered weight gain/loss as one such monitoring tool. Since pulmonary tuberculosis is endemic in this country, we take the opportunity to evaluate weight gain and chest radiograph, compared to sputum AFB smear in monitoring patient’s response. Methods: This was a retrospective study of confirmed positive sputum AFB smear patients from January 1999 to December 2004 who attended the Chest Clinic at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. Data on weight, chest radiograph and sputum AFB smear from initiation of therapy to end of treatment and follow-up were collected and analyzed. Results: 201 patients were included. At week-4 of anti-tuberculous treatment, only 14.7% had positive sputum smear. At completion of therapy 93.1% had improved chest radiographs. 90% had weight gain, 5% had weight loss and the remaining had no change in weight. Amongst patients with weight loss, there were no significant differences in the underlying illnesses (p=0.376), sputum smear at 4 weeks (p=0.697) and chest X-ray changes (p=0.731). Three patients who initially showed sputum smear conversion had reappearance of positive smear results towards the end of treatment. One of them was diagnosed as treatment failure while the other two remained well after discontinuation of therapy. Conclusion: Weight gain is very common among smear-positive tuberculosis patients after treatment even though weight gain does not correlate well with underlying disease, sputum conversion and chest X-ray changes. Reappearance of smear-positive sputum must be interpreted with caution and not to be regarded as treatment failure without other evidence